Implementasi Metode Relational Unified Process Dalam Pembuatan Sistem Penjadwalan Bimbingan Tugas Akhir - Pamungkas, I Kadek Krisna Angga; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro, 2020)
Abstract — Final project is one of the requirements that must be passed by students to complete their education. In the process of making the final project there is a guidance stage for the work of lecturers. The construction of the final assignment guidance scheduling system using the Relational Unfied Proccess (RUP) method aims to meet between lecturers and students, it is difficult to determine the schedule of meetings. In the RUP process there are 4 stages that must be passed in building a system. Inception at this stage the search for system requirements. Conducted by conducting interviews with students obtained a schedule for system development, 5 main functional needs of the system and 3 actors contained in the system. Elaboration is done by designing a system using the Unified Modeling Language. Beginning with the design with a use case diagram, proceed to the activity diagram and finally use the class diagram. The construction phase of the system is built based on the web using the programming languages ??PHP, HTML and CSS. Finally, in the transition phase the implementation at the construction stage will be tested using the blackbox method to test the functional system. In testing conducted on the login, submission of guidance, complaints and confirmation of submission obtained valid results for testing.